PELATIHAN BANTUAN HIDUP DASAR DAN RESUSITASI JANTUNG PARU, SERTA BAKTI SOSIAL KESEHATAN BERSAMA PAPDI MALUKU DI DESA WAHAI, SERAM UTARA - Kusadhiani, Indrawanti; Rahawarin, Halidah; Irwan, Irwan; Hataul, Is Asmaul Haq; Qisthi, Dian; Pattinasarany, Joane Christy Agavera; Ridy, Rizal Kurniawan; Marahena, Dhea Ananda; Akas, Ignasius Dede Setyo (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community engagement program was designed to strengthen the knowledge and skills of residents in Wahai Village, North Seram, in responding to medical emergencies such as sudden cardiac arrest, choking, and loss of consciousness. The primary focus was on Basic Life Support (BLS) and Cardiopulmonary Resuscitation (CPR), as timely intervention is widely recognized to improve survival outcomes before professional medical assistance becomes available. The program was implemented through structured health education, demonstrations, guided hands-on practice, and case-based simulations to ensure comprehensibility and applicability for the general community. In addition to the training, a social service initiative was conducted, providing free medical care including general health examinations, specialist consultations, and distribution of essential medications. The activity was delivered by a multidisciplinary health team comprising general practitioners, specialists, and medical students, in collaboration with the Indonesian Society of Internal Medicine (PAPDI) Maluku. The outcomes demonstrated strong community participation, enhanced first aid competence, and improved communication between healthcare providers and the community. This program is expected to foster greater community preparedness in emergencies and reinforce their role in preventive and promotive health efforts.